Excited states of mono- and biruthenium(II) complexes adsorbed on nanocrystalline titanium dioxide studied by electroabsorption spectroscopy - Daniel Pelczarski; Błażej Gierczyk; Maciej Zalas; Malgorzata Makowska-Janusik; Waldemar Stampor (Scientific Reports)
Abstract Comprehensive characterization of the lowest energy electronic excited states for mono- and binuclear Ru(II) complexes containing bipyridine ligands has been performed by electroabsorption (EA) spectroscopy. The EA spectra of Ru complexes sensitizing a TiO2 semiconductor were compared with the spectra of these complexes in the form of solid neat films, both of which parametrized within the Liptay theory. The extracted values of relevant parameters, relating to molecular dipoles after optical MLCT (metal-to-ligand-charge-transfer) excitation, exhibit a clearly noticeable increase for Ru complexes adsorbed on TiO2, but they are too small to be attributed to excitation associated with the direct transfer of an electron from the dye adsorbate to the TiO2 semiconductor. Due to the difficulties arising from standard analysis based on Liptay formalism, we have for the first time successfully reproduced the EA spectra of the Ru/TiO2 systems using the time-dependent density functional (TDDFT) calculations, incorporating into the Hamiltonian a term describing the interaction of a molecule with the local electric field it experiences from the TiO2 structure and the neighboring Ru complex molecules, without additional assumptions about the lineshape of the EA signal. The implications of these results are briefly discussed in the context of dye-sensitized solar cells.